Cybersecurity managing systems,conducting testing, and investigating intrusions - Mowbray, Thomas J. (John Wiley & Sons, 2014)
A must-have, hands-on guide for working in the cybersecurity profession Cybersecurity involves preventative methods to protect information from attacks. It requires a thorough understanding of potential threats, such as viruses and other malicious code, as well as system vulnerability and security architecture